Basal ganglia effects of GPi-DBS in cervical dystonia - Kojo, Vili (My University, 2024)
Dystonia is a movement disorder which has been linked to basal ganglia dysfunction. Still the pathophysiology of dystonia continues to be disputed and remains unclear for the time being. Deep brain stimulation (DBS) targeted to the globus pallidus internus (GPi) is an effective treatment option for medication refractory cervical dystonia. In spite of the clinical improvement that can be achieved, the mechanism by which DBS produces this benefit is not fully understood. The aim of this thesis was to study the effect which GPi-DBS induces on the glucose metabolism in the interconnected nuclei of the basal ganglia. Region of interest analyses were conducted to investigate the differences of metabolism with DBS turned on and off using 18F-fluorodeoxyglucose positron emission tomography images from eleven cervical dystonia patients. The results show that stimulation significantly increases brain glucose metabolism in the subthalamic nucleus and putamen. Furthermore, glucose metabolism change in GPi was found to correlate with regions of the inhibitory motor pathways. The findings also show that there is no relationship between glucose metabolism of these nuclei and clinical improvement, which may be explained by the network-wide effect of DBS. In conclusion, metabolic activity is increased by GPi-DBS in interconnected nuclei of the inhibitory pathways of basal ganglia. The increased activity is correlated between stimulated nucleus and other regions of the inhibitory pathways. Change of activity in individual nuclei of the basal ganglia induced by neurostimulatory treatment does not directly lead to the clinical benefit.
Keywords: basal ganglia, brain glucose metabolism, cervical dystonia, deep brain stimulation, positron emission tomography.